Surrounding Bacon & Warhol. - Dahlström, Per; Kvaran, Gunnar B.; Arbu, Grete (Göteborg : Göteborgs Konstmuseum, 2012)
Billgren, Ola ; Blake, Peter ; Canogar, Rafael ; Caulfield, Patrick ; Erro ; Fahlström, Öyvind ; Franzen, John E. ; Hockney, David ; Immendorff, Jörg ; Kippenberger, Martin ; Kirkeby, Per ; Brooks Kitaj, Ronald ; Lichtenstein, Roy ; Morley, Malcolm ; Nevelson, Louise ; de Saint-Phalle, Niki ; Polke, Sigmar ; Svedberg, Lena ; Östlihn, Barbro.
Tentoonstelling 'Surrounding Bacon & Warhol', Göteborgs Konstmuseum, Göteborg, 17.03.2012 - 12.08.2012.
Engels
Zweeds
boek
Keywords: Bacon, Francis; Warhol, Andy